Performance Optimization of Low-Cost DC Motors for Educational Engineering Applications - Singh, Vikram (Yayasan Kawanad, 2025)
This research examines how to build and improve a basic direct current (DC) electric motor using affordable, everyday materials for classroom teaching. We constructed our motor from simple components: copper wire coils, an iron nail, permanent magnets, and standard batteries. The device effectively demonstrates electromagnetic principles and energy conversion processes that students can observe firsthand. Our experimental work concentrated on three main factors that affect motor performance: the number of wire turns in the coil, magnet strength, and battery voltage levels. We systematically tested different combinations to find the best rotational speed and energy efficiency. The results showed interesting patterns - when we increased coil turns from 50 to 100, the motor's torque improved by roughly 20%. Using stronger magnets made the rotation much more stable and consistent. The motor worked most efficiently when powered by a 9-volt battery, where energy waste dropped to minimal levels. What makes this design particularly valuable is its simplicity - teachers can easily replicate it even in schools with limited resources, especially in Indian secondary education settings where budget constraints often limit hands-on learning opportunities. To verify our physical experiments, we ran computer simulations using finite element analysis. These digital models confirmed our real-world findings and revealed that optimized coil arrangements increased magnetic flux density by 15%. The close agreement between our experimental data and simulation results strengthens confidence in the design approach. This motor design offers teachers and students a practical, affordable way to explore electromagnetism and basic engineering principles. The project has broader implications for educational programs in developing regions, where cost-effective teaching tools can make advanced concepts accessible to more students. Schools can now demonstrate complex electromagnetic theory using materials that cost less than traditional laboratory equipment while achieving comparable learning outcomes.